La vulnerabilidad social en la intersección de variables tangibles e intangibles: una propuesta desde un abordaje inductivo - Gomes, Mafalda (Universidad Estatal a Distancia, Costa Rica, 2022)
This paper aims to analyse social categories related to vulnerability through a qualitative approach. This reflection is based on sociology of poverty, and social vulnerability, with contributions from the theory of intersectionality and the concept of social disintegration. Through this approach, social vulnerability is a plural concept that results from the intersection of social positions, life experiences, and skills. The characteristics of social groups in situations of vulnerability will be examined through interviews with social workers in social economy organisations. The outcomes indicate that social vulnerability results from the intersection of socio-demographic and economic factors that weaken the educational and professional trajectory of people in situations of vulnerability, particularly about their social and emotional competencies. From this inductive approach, we propose an intersection of tangible and intangible variables to characterize the complex profile of people experiencing social vulnerability.